# Laplace Transform of Bessel Function of the First Kind/Proof 1

## Theorem

Let $J_n$ denote the Bessel function of the first kind of order $n$.

Then the Laplace transform of $J_n$ is given as:

$\laptrans {\map {J_n} {a t} } = \dfrac {\paren {\sqrt {s^2 + a^2} - s}^n} {a^n \sqrt {s^2 + a^2} }$

## Proof

 $\ds \map {J_n} {a t}$ $=$ $\ds \dfrac {\paren {a t}^n} {2^n \, \map \Gamma {n + 1} } \paren {1 - \dfrac {\paren {a t}^2} {2 \paren {2 n + 2} } + \dfrac {\paren {a t}^4} {2 \times 4 \paren {2 n + 2} \paren {2 n + 4} } - \cdots}$ $\ds$ $=$ $\ds \sum_{k \mathop = 0}^\infty \dfrac {\paren {-1}^k} {k! \, \map \Gamma {n + k + 1} } \paren {\dfrac {a t} 2}^{n + 2 k}$

Hence:

 $\ds \laptrans {\map {J_n} {a t} }$ $=$ $\ds \laptrans {\sum_{k \mathop = 0}^\infty \dfrac {\paren {-1}^k} {k! \, \map \Gamma {n + k + 1} } \paren {\dfrac {a t} 2}^{n + 2 k} }$ $\ds$ $=$ $\ds \sum_{k \mathop = 0}^\infty \dfrac {\paren {-1}^k a^{n + 2 k} } {2^{n + 2 k} k! \, \map \Gamma {n + k + 1} } \laptrans {t^{n + 2 k} }$ Linear Combination of Laplace Transforms $\ds$ $=$ $\ds \sum_{k \mathop = 0}^\infty \dfrac {\paren {-1}^k a^{n + 2 k} } {2^{n + 2 k} k! \, \map \Gamma {n + k + 1} } \dfrac {\map \Gamma {n + 2 k + 1} } {s^{n + 2 k + 1} }$ Laplace Transform of Power $\ds$ $=$ $\ds \sum_{k \mathop = 0}^\infty \paren {-1}^k \paren {\dfrac a 2}^{n + 2 k} \dfrac {\map \Gamma {n + 2 k + 1} } {k \, \map \Gamma k \, \map \Gamma {n + k + 1} } \dfrac 1 {s^{n + 2 k + 1} }$ rearrangement, Gamma Function Extends Factorial $\ds$ $=$ $\ds \sum_{k \mathop = 0}^\infty \paren {-1}^k \paren {\dfrac a 2}^{n + 2 k} \dfrac 1 {k \, \map \Beta {k, n + k + 1} } \dfrac 1 {s^{n + 2 k + 1} }$ Definition 3 of Beta Function